O03 Allergy to penicillins in a pediatric population: reported vs true. Issue 6 (17th May 2019) - Elzagallaai, AA; Gill, H; Rieder, MJ
Abstract : Background: Reported allergy to penicillins is a major clinical problem. Over 10% of parents report drug allergy resulting in higher cost and less than optimum management of infectious diseases. Objectives: To determine the relative likelihood of true allergy in patients suspected to have a penicillin allergy and to investigate the risk factors involved. We hypothesized that the vast majority of self-reported penicillin allergies are less likely to be true allergies when proper immunological work up is performed. Methods: Paediatric patients aged 0–18 years presenting to the ADR clinic at the Children Hospital of Western Ontario (CHWO) with suspected antibiotic allergies were included. A retrospective review of charts was conducted to obtain demographic information and results from allergological and in vitro testing. Subjects were evaluated with a radioallergosorbent test (RAST) or the lymphocyte toxicity assay (LTA)/the in vitro platelet toxicity assay ( i PTA) depending on whether the history was most consistent with an immediate allergy or a delayed hypersensitivity, respectively. Patients with negative RAST or LTA/iPTA were recommended to undergo confirmatory oral challenge test (OCT). Results: Ninety subjects were identified including 75 with possible penicillin allergy and 10 with suspected allergy to a non-penicillin antibiotic. Five subjects presented with a mixed allergy. Based on the results from RAST, in vitro testing and OCTs, the prevalence of a true allergy in the penicillin group was 6.25% vs. 66.67% in the non-penicillin group (p< 0.001). Patients presenting with severe reactions were more likely to be truly allergic (p< 0.01). In-patients were more likely to present with non-penicillin allergies and were subsequently more likely to have a true allergy (p< 0.001). Conclusions: True allergy is very rare in patients with suspected penicillin allergies and can be determined with a proper work-up including OCT. Shorter protocols for the evaluation of these patients would be beneficial. Disclosure(s): Nothing to disclose